1993
DOI: 10.1111/j.1423-0410.1993.tb02172.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of the MAIEA Technique to Confirm the Relationship between the Cromer Antigens and Decay‐Accelerating Factor and to Assign Provisionally Antigens to the Short‐Consensus Repeats

Abstract: The MAIEA (monoclonal-antibody-specific immobilisation of erythrocyte antigens) assay has recently been developed for the assignment of red cell antigens, recognised by human alloantisera, to particular membrane components of the red cell membrane. This technique detects trimolecular complexes formed by the reaction of a human antibody and a mouse antibody with a particular red cell protein. A positive reaction, in an ELISA-type detection procedure, occurs if the epitopes to the human and mouse antibodies are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 19 publications
(9 reference statements)
0
13
0
Order By: Relevance
“…The technique was successful and included some preliminary results on some of the Kell antigens [17]. Another study confirmed the relationship between the Cromer system antigens and decay-accelerating factor, and also provisionally assigned antigens to the different short consensus repeats [18].…”
Section: Introductionmentioning
confidence: 84%
“…The technique was successful and included some preliminary results on some of the Kell antigens [17]. Another study confirmed the relationship between the Cromer system antigens and decay-accelerating factor, and also provisionally assigned antigens to the different short consensus repeats [18].…”
Section: Introductionmentioning
confidence: 84%
“…Cromer specificity was confirmed in the monoclonal antibody immobilization of erythrocyte antigens (MAIEA) assay (Petty, 1993). Positive ratios were obtained with the following murine monoclonal anti‐DAF: BRIC 230 (SCR1), BRIC 110 (SCR2) and BRIC 216 (SCR3) (Petty et al ., 1993). BRIC 216 produced lower ratios (3·2, compared to 10·7 for BRIC 230 and 5·3 for BRIC 110) suggesting that partial inhibition had occurred.…”
Section: Case Studymentioning
confidence: 99%
“…Monoclonal Antibody-Specific Immobilisation of Erythrocyte Antigens This method has been described in more detail elsewhere [17,18]. Briefly, 80 pi of 10% washed red cell suspensions were incubated with 40 pi of mouse monoclonal antibody and 40 pi of human sera for 60 min at 37°C.…”
Section: Absorb Ancementioning
confidence: 99%